Indigenisation and technological change at the firm level-the case of the black and white TV picture tube - Kharbanda, V. P. (Technovation)
The study analyses the technological change process at the firm level by taking a case study of the black and white TV picture tube technology in India. The process of absorption and adaptation of imported technologies has been examined in three different firms. The study shows that the public sector firm has been very effective in building up indigenous technological capability, i.e. 'technoware' and 'humanware', and the subsequent diffusion of technology and expert manpower. However because of weak 'orgaware', efficiency was low and thus the firm could not compete in the market place. In contrast, 'Firm B', managed by an NRI entrepreneur, could perform better because of strong management of the orgaware, and thus dominated the market. The study confirms that the 'learning by doing' process at the shop floor helps to a great extent in the absorption and adaptation of imported technologies. It is concluded that, along with efforts at in-house R&D, sustained strong linkages have to be built up at the firm level with national R&D institutions and laboratories in order to compete in the international market.